Mass Propagation of Agarwood Producing Plant (Aquilaria Malacensis L.) with Application Auxin and Cytokinine Concentrations in Vitro Culture - Satria, Benni; Martinsyah, Rachmad Hersi; Warnita, Warnita (International Journal of Environment, Agriculture and Biotechnology, 2021)
The objective of study to obtain: the best concentration of thidiazuron in encouraging explants to form shoots and the best combination of concentrations of NAA and BAP to regenerate callus and shoots to form plantlets. This experiment was carried out in Plant Tissue Culture Laboratory, Faculty of Agriculture Andalas University from May to October 2021. This study consisted of two experimental stages. where the first stage to callus induction with 6 levels of Thidiazuron concentration: 0.00, 0.125, 0.250, 0.375, 0.50 and 0.625 ppm. The second stage of the experiment was the shoot and callus regeneration stage with a combination treatment of NAA + BAP concentration, with 7 levels of treatment: 0.0 ppm NAA + BAP 0.0 ppm; 0.0 ppm NAA + 1.00 ppm BAP; 0.0 ppm NAA + 2.0 ppm BAP; 0.0 ppm NAA + 3.0 ppm BAP; 0.50 ppm NAA + 1.0 ppm BAP; 0.5 ppm NAA + 2.0 ppm BAP and 0.50 ppm NAA + 3.0 ppm BAP. The study was completely randomized design (CRD) with 3 replications in a The data were analyzed by using the F test and followed by the Least Significant Difference test (LSD). The experiment was conducted with completely randomized design with 3 replications. The result show the highest percentage of live explants was 100%, the fastest time callus induction was 15 days and the percentage of explants formed callus of was 70% at treatment with a concentration of 0.25 ppm Thiduazuron. The callus structure of all treatment levels was compact and the color of the callus was white, yellowish white and whitish yellow. callus forming the fastest shoots was 11.67 days, the percentage of callus forming shoots was 50% and the number of callus forming shoots was 5 pieces obtained at a concentration of 0.5 ppm NAA + 3.0 ppm BAP.